Optical Efficiency Analysis of Primary Mirror in LFR-CSP. Issue 1 (1st April 2022) - Lv, Hongwei; Chen, Kang; Chen, Pengfei; Wang, Xiao; Wen, Long
Abstract: The linear Fresnel solar thermal power generation system is one of the most representative forms of solar thermal power generation system at present. The primary mirror, as the main mirror, plays a key role in the photothermic conversion process of the collector tube. In this paper, the solar position and the optical efficiency of the primary mirror in LFR-CSP are modeled and analyzed. The light reflection process of primary mirror by solar position through four dimensions of solar declination angle, solar time angle, altitude angle and azimuth angle is studied, and the distribution law of solar position parameters in different seasons and different times throughout the year is analyzed. It is found that the variation range of chord efficiency of a single mirror element in the whole day is 75 %-93 %. The position of a mirror element in winter solstice has the greatest impact on the end loss of more than 1 %, but the summer solstice has no effect.